Superselective Angioembolisation: A Report of Two Rare Cases of Hemoptysis - Keshmiri, Mohammad Sadegh; Sharifkashani, Babak; Serati, Alireza; Seyedi, Seyed Reza; Naghashzadeh, Farah; Salehi, Siroos; Dehghan, Omid (International Journal of Cardiovascular Practice, 2019)
Superselective bronchial embolization is recently performed with a high success rate. The current study aimed at discussing the procedure and reporting two cases underwent embolization in the Masih-Daneshvari Hospital, a large center for this procedure, in Iran.